Shattered past : reconstructing German histories - Jarausch, Konrad H. (Konrad Hugo), 1941-; Geyer, Michael, 1947- (Princeton, N.J. : Princeton University Press, 2003)
Broken glass, twisted beams, piles of debris--these are the early memories of the children who grew up amidst the ruins of the Third Reich. More than five decades later, German youth inhabit manicured suburbs and stroll along prosperous pedestrian malls. Shattered Past is a bold reconsideration of the perplexing pattern of Germany's twentieth-century history. Konrad Jarausch and Michael Geyer explore the staggering gap between the country's role in the terrors of war and its subsequent success as a democracy.
A return to national history? The master narrative and beyond -- The collapse of the counternarrative: coping with the remains of socialism -- Modernization, German exceptionalism, and post-modernity: transcending the critical history of society -- War, genocide, extermination: the war against the Jews in an era of world wars -- The totalitarian temptation: ordinary Germans, dictatorship, and democracy -- From empire to Europe: the taming of German power -- Unsettling German society: mobility and migration -- A struggle for unity: redefining national identities -- Defining womanhood: the politics of the private -- In pursuit of happiness: consumption, mass culture, and consumerism -- Survival in catastrophe: mending broken memories -- The century as history: between cataclysm and civility.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Historiography -- Germany -- History -- 20th century; History -- Philosophy; Nationalism -- Germany -- History -- 20th century; Holocaust, Jewish (1939-1945) -- Historiography; Germany -- Social conditions -- 20th century; Historiographie -- Allemagne -- Histoire -- 20e siècle.; Histoire -- Philosophie; Nationalisme -- Allemagne -- Histoire -- 20e siècle.; Holocauste, 1939-1945 -- Historiographie; Allemagne -- Conditions sociales -- 20e siècle.; HISTORY; HISTORY -- Europe -- Germany; Historiography; History -- Philosophy; Nationalism; Social conditions; Germany; Geschiedschrijving; Politieke geschiedenis; Sociale geschiedenis; Paradigma's.; Natie; Internationalisatie; 1900-1999; History